Local Employer and Union Perceptions of Two-Tier Bargaining - Gallagher, Daniel; Wetzel, Kurt (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1984)
This study examines local union and employer views of the concept and operation of a two-tier bargaining structure for teacher contract negotiations in Saskatchewan. The results are based on a survey of 138 local union and trustee representatives' views of collective bargaining under a centralized multiemployer arrangement with supplementary local negotiations.